Impact of Temperature and Doping on the Performance of ${{\bf Ge}}/{{\bf G}}{{{\bf e}}_{1 - {\boldsymbol{x}}}}{{\bf S}}{{{\bf n}}_{\boldsymbol{x}}}/{{\bf Ge}}$ Heterojunction Phototransistors - Harshvardhan Kumar; Rikmantra Basu; Guo-En Chang (IEEE Photonics Journal, 2020)
We study the effect of temperature and doping in Si-based GeSn heterojunction phototransistors (HPTs) for low-power-consuming, low-cost, and high-speed mid-infrared (MIR) applications. The incorporation of ${\rm{G}}{{\rm{e}}_{1 - x}}{\rm{S}}{{\rm{n}}_x}$ alloy in the base of our HPTs significantly shortens the emitter-to-collector transit time, leading to high cut-off frequency ( ${f_T}$ ) due to an increase in mobility. Furthermore, the ${\rm{G}}{{\rm{e}}_{1 - x}}{\rm{S}}{{\rm{n}}_x}$ base extends the optical detection over a wide range (up to 2500 nm) due to the shrinkage of the bandgap energy caused by alloying with Sn. Additionally, spectral responsivity increases with Sn alloying due to the increased absorption coefficient. Our results show that ${f_T}$ and responsivity are strongly dependent not only on doping but also on temperature. The impact of temperature on the noise behavior of phototransistors was also analyzed for frequencies up to 100 GHz. As the temperature increased, the signal-to-noise ratio (SNR) decreased; however, spectral responsivity significantly improved. The high SNR, responsivity, and ${f_T}$ values of the GeSn HPT make it a potential candidate for future Si-based uncooled high-speed MIR photodetection.